The Potential Of Mangosteen Bark Extract As A Natural Preservative For The Quality Of Aren Nira During Tapping - Nina Juliana Roberta Turnip; Claudia A. Ginting; Merry M. Martgrita; Astiti Aditia (Jurnal Pangan dan Agroindustri, 2025)
Abstract